Assessment of Adipose Tissues as a Risk Factor for Cardiovascular Diseases among Students of a Nigerian Tertiary Institution - Adesola Ojo Ojoawo; Rufus Adesoji Adedoyin; Adedayo A Adekoyejo; Taofeek Oluwole Awotidebe (International Journal of Medical Research, 2014)
Introduction: The purpose of this study was to assess adipose tissues distribution. This was with a view of establishing risk for development of CVD among this population. Method: One hundred and ninety apparently healthy undergraduate students (100 males and 90 females), mean age of 24.29 + 3.54 years participated in the study. The following variables were measured using standard protocols; weight, height, skin fold thickness, waist circumference and hip circumference. Data were analysed using descriptive and inferential statistics. Result: Result revealed that fewer percentage of participants were obese using body mass index (BMI) (male, 21.0% overweight, 5.0% obese; female, 37.8% overweight); waist to hip ratio, (male 57.0 % overweight, female, 26.7 overweight, 31.1% obese), waist circumference, (male 100% overweight) and waist to height ratio (WHtR), (male,11.0 % overweight, female 4.4% overweight). Male have significant higher weight, BMI, WC, WHR, WHtR than female participants (p< 0.05). There was a significant association between age and BMI (p< 0.01), and age and WHtR (p= 0.023). Conclusion: It can be concluded from the study that average participants were not obese at the time of the study; hence they may not be at risk of CVD. Body Mass Index of male participants were significantly more than that of female but percent body fat of female were significantly higher than that of male. Age and sex were individually associated with level of adiposity.